2014
DOI: 10.1093/humrep/deu191
|View full text |Cite
|
Sign up to set email alerts
|

Estimated disability-adjusted life years averted by long-term provision of long acting contraceptive methods in a Brazilian clinic

Abstract: This study received partial financial support from the Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), grant # 2012/12810-4 and from the National Research Council (CNPq), grant #573747/2008-3. B.F.B., M.P.G., and V.M.C. were fellows from the scientific initiation programme from FAPESP. Since the year 2001, all the TCu380A IUD were donated by Injeflex, São Paulo, Brazil, and from the year 2006 all the LNG-IUS were donated by the International Contraceptive Access Foundation (ICA), Turku, Finland.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 30 publications
0
36
0
3
Order By: Relevance
“…Conversely, the sales of LARC methods, the most effective contraceptive methods, have been very low, [18][19][20] even during the recent Zika virus outbreak. 21 This reflects the fact that most women are using contraceptive methods such as COCs, progestin-only pills, injectable and emergency contraceptives, all of which are much less effective than LARC methods.…”
Section: 18mentioning
confidence: 99%
“…Conversely, the sales of LARC methods, the most effective contraceptive methods, have been very low, [18][19][20] even during the recent Zika virus outbreak. 21 This reflects the fact that most women are using contraceptive methods such as COCs, progestin-only pills, injectable and emergency contraceptives, all of which are much less effective than LARC methods.…”
Section: 18mentioning
confidence: 99%
“…One example was our evaluation of the last 10 years’ experience at a Brazilian family planning clinic based in Campinas. Our group estimated the contribution of the provision of LARC methods and the depot-medroxyprogesterone acetate injectable contraceptive to averted disability-adjusted life years (DALY; maternal mortality and morbidity, child mortality and abortions) and provided evidence about these indicators 2. The objective of the present study was to estimate the averted DALY11 among LNG-IUS users who received the device at no cost at 26 Brazilian teaching hospitals from 2007 to 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The levonorgestrel-releasing intrauterine system (LNG-IUS) is one of the most effective reversible contraceptives with a pregnancy failure rate between 0.01-0.3 per 100 womanyears [1,2] and also presents additional non-contraceptive benefits, such as control of heavy menstrual bleeding. [3] Furthermore, many researchers have reported that almost 90% of users were satisfied with this method at the end of the first year after placement.…”
Section: Introductionmentioning
confidence: 99%